Upregulation of Human Endogenous Retrovirus-K Is Linked to Immunity and Inflammation in Pulmonary Arterial Hypertension. Issue 20 (14th November 2017) - Saito, Toshie; Miyagawa, Kazuya; Chen, Shih-Yu; Tamosiuniene, Rasa; Wang, Lingli; Sharpe, Orr; Samayoa, Erik; Harada, Daisuke; Moonen, Jan-Renier A.J.; Cao, Aiqin; Chen, Pin-I; Hennigs, Jan K.; et al.
Abstract : Background: Immune dysregulation has been linked to occlusive vascular remodeling in pulmonary arterial hypertension (PAH) that is hereditary, idiopathic, or associated with other conditions. Circulating autoantibodies, lung perivascular lymphoid tissue, and elevated cytokines have been related to PAH pathogenesis but without a clear understanding of how these abnormalities are initiated, perpetuated, and connected in the progression of disease. We therefore set out to identify specific target antigens in PAH lung immune complexes as a starting point toward resolving these issues to better inform future application of immunomodulatory therapies. Methods: Lung immune complexes were isolated and PAH target antigens were identified by liquid chromatography tandem mass spectrometry, confirmed by enzyme-linked immunosorbent assay, and localized by confocal microscopy. One PAH antigen linked to immunity and inflammation was pursued and a link to PAH pathophysiology was investigated by next-generation sequencing, functional studies in cultured monocytes and endothelial cells, and hemodynamic and lung studies in a rat. Results: SAM domain and HD domain-containing protein 1 (SAMHD1), an innate immune factor that suppresses HIV replication, was identified and confirmed as highly expressed in immune complexes from 16 hereditary and idiopathic PAH versus 12 control lungs. Elevated SAMHD1 was localized to endothelial cells, perivascular dendritic cells, and macrophages, and SAMHD1 antibodies were prevalent in tertiary lymphoid tissue. An unbiased screen using metagenomic sequencing related SAMHD1 to increased expression of human endogenous retrovirus K (HERV-K) in PAH versus control lungs (n=4). HERV-K envelope and deoxyuridine triphosphate nucleotidohydrolase mRNAs were elevated in PAH versus control lungs (n=10), and proteins were localized to macrophages. HERV-K deoxyuridine triphosphate nucleotidohydrolase induced SAMHD1 and proinflammatory cytokines (eg, interleukin 6, interleukin 1β, and tumor necrosis factor α) in circulating monocytes, pulmonary arterial endothelial cells, and also activated B cells. Vulnerability of pulmonary arterial endothelial cells (PAEC) to apoptosis was increased by HERV-K deoxyuridine triphosphate nucleotidohydrolase in an interleukin 6-independent manner. Furthermore, 3 weekly injections of HERV-K deoxyuridine triphosphate nucleotidohydrolase induced hemodynamic and vascular changes of pulmonary hypertension in rats (n=8) and elevated interleukin 6. Conclusions: Our study reveals that upregulation of the endogenous retrovirus HERV-K could both initiate and sustain activation of the immune system and cause vascular changes associated with PAH. Abstract : Supplemental Digital Content is available in the text.